2009
DOI: 10.1371/journal.pone.0008343
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for the 12 Item WHO Disability Assessment Schedule 2.0

Abstract: BackgroundThe World Health Organization Disability Assessment Schedule (WHODAS 2.0) measures disability due to health conditions including diseases, illnesses, injuries, mental or emotional problems, and problems with alcohol or drugs.MethodThe 12 Item WHODAS 2.0 was used in the second Australian Survey of Mental Health and Well-being. We report the overall factor structure and the distribution of scores and normative data (means and SDs) for people with any physical disorder, any mental disorder and for peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
309
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 364 publications
(341 citation statements)
references
References 9 publications
25
309
6
1
Order By: Relevance
“…So far only one paper has reported on the feasibility of the revised WHODAS 2.0 12-item version. In a sample of the Australian general population 0.2% had missing data in one or more WHODAS 2.0 items administered by interview [11]. However, these results are hardly comparable with our study as they differ regarding the mode of administration (interview versus self-administered) and characteristics of the study population (age, health status, country of origin) [41].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…So far only one paper has reported on the feasibility of the revised WHODAS 2.0 12-item version. In a sample of the Australian general population 0.2% had missing data in one or more WHODAS 2.0 items administered by interview [11]. However, these results are hardly comparable with our study as they differ regarding the mode of administration (interview versus self-administered) and characteristics of the study population (age, health status, country of origin) [41].…”
Section: Discussioncontrasting
confidence: 91%
“…Sousa et al [12] examined unidimensionality of the WHODAS 2.0 in elderly people living in seven low-and middle-income countries and showed that principle component analysis gave rise to a one-factor solution in most countries. In the study from Andrews et al [11] a second-order one-factor solution with six first-order factors was the best-fitting model for the Australian general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the evidence that early diagnosis can improve outcomes [9,25]. Clinically important changes are represented in the QuickDASH as a change of 15 points [26]; WHODAS as 15 [27]; MPQ PRI as 5 with NRS as 3 [28]; FFI as 10 [21]. This sample shows significant clinical improvement across all measures 6 months after commencing physiotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the editors of the DSM-5 should consider the WHODAS 2.0 12-item as a sensible alternative to the WHODAS 2.0 36-item scale in new versions of this manual. Furthermore, despite isolated studies with people aged 15 to 17 years [23][24][25] and the release of an unofficial version directed at children and adolescents [26], one limitation of the WHODAS 2.0 is the fact that it is only recommended by the WHO for application in adults [4,5] and, consequently, use of the GAF should not yet be discontinued.…”
Section: Discussionmentioning
confidence: 99%